Prevalence and patterns of renal vascular variations among potential kidney donors: a Computed Tomography Angiography (CTA) study in Sudan - Osman, Sara; AbdAlla, Eltayeb; Ali, Ladin; MohamedAli, Hoyam; Taha, Baraa; Elmahdi, Tasneem S. A.; Mohammed, Safaa (BMC nephrology, 2025)
Anatomical variations in the renal vasculature complicate surgical techniques and necessitate meticulous preoperative planning. This study aims to ascertain the prevalence and patterns of renal vascular variations in potential kidney transplant donors at Ahmed Gasim Teaching Hospital, Khartoum, Sudan, via computed tomography angiography (CTA). A descriptive cross-sectional study was performed on 160 potential kidney donors who underwent renal CTA from January to December 2022. Data were collected via a checklist and analyzed with SPSS version 28. Variations in renal arteries, such as accessory renal arteries and premature bifurcations, have been reported and classified. Additional vascular variations were noted. Of the 160 subjects, 57.5% had normal single renal arteries bilaterally, whereas 42.5% had variations in renal artery anatomy. Accessory renal arteries were identified in 25.6% of the participants, whereas early branching occurred in 17%. Variations were more common in males, with 37% exhibiting accessory renal arteries compared with 16.1% in females (p = 0.008). Bilateral accessory renal arteries were identified in 3.8% of the donors. Circum-aortic left renal vein (1.3%) and Transposition of the inferior vena-cava (1.3%) were also detected. A notable prevalence of renal artery variations was identified among these potential Sudanese kidney donors, with accessory arteries and early branching being the most common. Recognising such variations is crucial for safe surgical planning and optimal outcomes in kidney transplantation. While this study utilised CT angiography to delineate these vascular patterns, the importance lies in employing accurate and reliable imaging assessments-of which CTA is one valuable option-to guide preoperative evaluation and reduce surgical risks. Not applicable (this is an observational study).